Exploring the genetic diversity within traditional Philippine pigmented Rice - Mbanjo, Edwige Gaby Nkouaya; Jones, Huw; Caguiat, Xavier Greg Isaguirre; Carandang, Socorro; Ignacio, John Carlos; Ferrer, Marilyn Cruz; Boyd, Lesley Ann; Kretzschmar, Tobias (Springer, 2019)
The wild ancestors of domesticated rice had red seed, white rice being the result of a mutation in the rice domestication gene Rc. Many pigmented rice landraces are still grown by ethnic communities for their nutritional and cultural value. This study assesses the genetic diversity in a collection of pigmented rice accessions from the Philippines We undertook an analysis of the genetic and colour variation in a collection of 696 pigmented rice accessions held at PhilRice in the Philippines. The collection was reduced to 589 genotypes after removal of accessions with limited passport data or with low SNP marker call rates. Removal of duplicate genotypes resulted in a final, core collection of 307 accessions, representing all administrative districts of the Philippines, and composed predominately of japonica and indica sub-species. No genetic structure was observed in the core collection based on geographic origin. A pairwise comparison of accessions by region indicating that both local and long-distance exchange of rice accessions had occurred. The majority of the genetic variation was within regions (82.38%), rather than between regions (10.23%), with the remaining variation being within rice accession variance (7.39%). The most genetically diverse rice accessions originated from the Cordillera Administrative Region (CAR) in the far north of the Philippines, and in the regions of Davao and Caraga in the southeast. A comparison with pigmented rice accessions from the neighbouring countries Taiwan, Laos, China and India revealed a close relationship between accessions from Taiwan, supporting the hypothesis of southward diffusion of Austronesians from Taiwan to the Philippine. The 14-bp deletion within the gene Rc, known to result in loss of red pigmentation, was found in 30 accessions that still had coloured pericarps. Multi-spectral phenotyping was used to measure seed geometric and colour-appearance traits in 197 accessions from the core collection. The purple and variable purple rice accessions had the lowest values for the seed colour parameters - lightness (L*), intensity, saturation, a* (green – red; redness) and b* (blue – yellow; yellowness) These pigmented rice accessions represent a diverse genetic resource of value for further study and nutritional improvement of commercial rice varieties.